√3(x-2)-2√2x=2(√3x-√2x-3)
Răspunsuri la întrebare
Răspuns de
0
V3x-2V3-2V2x=2V3x-2V2x-6
V3x-2V3x+2V2x-2V2x=2V3-6
-V3x=2V3-6
V3x=6-2V3
x=(6-2V3)/V3=V3(6-2V3)/3=(6V3-6)/3=3(2V3-2)/3=2V3-2
V3x-2V3x+2V2x-2V2x=2V3-6
-V3x=2V3-6
V3x=6-2V3
x=(6-2V3)/V3=V3(6-2V3)/3=(6V3-6)/3=3(2V3-2)/3=2V3-2
Alte întrebări interesante
Matematică,
8 ani în urmă
Studii sociale,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă